Zinc and gut microbiota in health and gastrointestinal disease under the COVID‐19 suggestion. (26th February 2022) - Scarpellini, Emidio; Balsiger, Lukas M.; Maurizi, Valentina; Rinninella, Emanuele; Gasbarrini, Antonio; Giostra, Nena; Santori, Pierangelo; Abenavoli, Ludovico; Rasetti, Carlo
Abstract: Microelements represent an emerging resource for medicine and its preventive branch. Zinc is the second most abundant element in our organism with peculiar physiologic functions and pathophysiologic implications in systemic and gastrointestinal (GI) diseases. It interacts very often with gut microbiota (GM) and can affect natural course of GI diseases through a bidirectional relationship with intestinal bugs. We aimed to review literature data regarding zinc chemistry, role in health, and GI diseases in man with a special focus on its interaction with GM. We conducted a search on the main medical databases for original articles, reviews, meta‐analyses, randomized clinical trials and case series using the following keywords and acronyms and their associations: zinc, microelements, gut microbiota, gut health, and COVID‐19. Zinc has a rapid and simple metabolism and limited storage within our body. Its efficacy on immune system modulation reflects on improved response to pathogens, reduced inflammatory response, and improved atopic/allergic reactions. Zinc is also involved in cell cycle regulation (namely, apoptosis) with potential anti‐cancerogenic effects. All these effects are in a "symbiotic" relationship with GM. Finally, zinc shows preliminary viral antireplicative effects. Zinc seems to gain more and more evidences on its efficacy in allergic, atopic and infectious diseases treatment, and prevention. COVID‐19 can be the booster for research on future applications of zinc as perfect "postbiotic" in medicine.